College Students’ Perspectives on Academic Procrastination : Their Perceived Causes, Consequences, and Interventions - Pyong Ho Kim (International Journal of Advanced Culture Technology(IJACT), 2025)
Academic procrastination refers to learners’ deliberate delaying behavior on given tasks, even when acknowledging adverse consequences of their actions. Though its causes are manifold, research shows that procrastination usually results in negative outcomes, such as anxiety, depression, lower self-esteem, and impaired educational attainment. We attempted to examine college students’ procrastinating pattern in academic pursuits, focusing on their perceived causal factors, consequences, and means of resolutions to reduce related behavior. 12 undergraduate students enrolled in South Korea responded to a questionnaire that contained openended, Likert scale, and multiple-choice format items. Findings revealed the student participants’ multifaceted determinants of procrastination that consist of emotional, social, and psychological factors. They recognized avoidance of multitasking, chunking down tasks into smaller pieces, and effective planning as helpful strategies to cope with procrastination. While some acknowledged benefits of procrastination, they appeared to be skeptical about fixing their postponing habit. The results of the present study addressed and highlighted a need for interventions designed to meet and resolve the diverse challenges of procrastinating students. Relevant topics are discussed for future researchers.